Will information technology create a new notion of education much wider than the school frontiers? - Kibbi, Ibrahim (Beirut Ligue des Professeurs de l'U.L, 2007)
Will information technology create a new notion of education much wider than the school frontiers? This paper will answer this question by discussing the topics that deal with integrated communities of learning and their effect in the Arab world. The topics are: the cooperative learning communities integrated community services for children and their families, innovative curricular models that foster collaborative communities of learners within the classroom, and telementoring relationships among learners, and providing effective schooling for students at risk. As a result, this paper shows that everybody is involved in improving students$1 (Blearning. Students, teachers, schools, and communities should work together to achieve their goals. The teacher, as a mediator, provides communication and the sharing of knowledge among students and teachers. Students$1 (Bwork should always be evaluated and the results should be discussed with parents who are responsible for developing problem solving skills and social relationships among students. Also, technology such as the media enables the development of new learning. Computer-mediated learning improves students$1 (Blanguage skills such as reading, comprehension, and writing. Therefore, the Internet improves students$1 (Bcommunication, knowledge, and social skills as well as it improves teacher education.s
(3GdfhY (B: Articles
Keywords: Education et la technologie; Educational prospective; ICT and Education; Prospective; (3GdGSJTQGas; (3GdJYdje hGdJcfhdhLjGs